If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -8 + 14x = -34 Reorder the terms: -8 + 1x + 14x = -34 Combine like terms: 1x + 14x = 15x -8 + 15x = -34 Solving -8 + 15x = -34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 15x = -34 + 8 Combine like terms: -8 + 8 = 0 0 + 15x = -34 + 8 15x = -34 + 8 Combine like terms: -34 + 8 = -26 15x = -26 Divide each side by '15'. x = -1.733333333 Simplifying x = -1.733333333
| p+3.1=18 | | x-27=62 | | -6y/2+2/2+3y/2=-10y/8+8/8 | | 6x-2=1.25(3x-8) | | 11-6x=6x-1 | | x+7.4=23.5 | | 12z+(13z-14)=-(26z-25)-9+20z | | 60=z-113 | | 11-6x=6c-1 | | 2X-14=-8 | | m+10/-2=5 | | -2x+6(2-x)-4=3(x+1)-6 | | -4y/3+6=-y/2+3 | | 6x-9+2x=79 | | 3(4K+7)=19K | | 9x=37.8 | | s+1.3=18 | | 6x+15=3x+3 | | a=-169/-13 | | 4/3+2Y=4Y-1/6 | | 23-9y+(26y-19)=-27 | | 3*1.8+1.2=6*1.8-0.3 | | -2x/2-12/2+7/4-3x/8-9/8 | | -4-6x+7x=-3 | | 12x-13x(x+4)=4x-6 | | (5.6p+.3p)+7.1=-2.2 | | 4(5y+3)=3(2y-5)- | | -14+t=26.5 | | (4x+1)/4-(2x+3)/3=7/12 | | 3(1.8+1.2)=6(1.8-0.3) | | 900+b^2=6400 | | 23x-41=54x+21 |